CAPE HORN: A BIOGEOGRAPHIC MELTING POT AT THE SOUTHERN END OF THE AMERICAS - Rozzi Marin, Ricardo Roberto (My University, 2018)
In this work, I propose to distinguish three discoveries of Cape Horn. A first discovery would have occurred about 7500 years ago, when the ancestors of the Yahgan people arrived to the archipelagos located south of Tierra del Fuego. A second discovery took place in 1616, when Dutch explorers spotted Cape Horn and transformed the paradigm of the seventeenth century European cartography that represented Tierra del Fuego attached to the Antarctic Continent. A third discovery occurred in 2005, when UNESCO created the Cabo Cape Horn Biosphere Reserve (RBCH), based on the discovery of an exceptional richness of bryophytes (mosses and liverworts) and lichens. This finding transformed the southern end of the Americas into a world center of biodiversity for these groups of organisms. I present a special attribute of Cape Horn's biodiversity: its multiple biogeographical relationships. For Cape Horn's biodiversity, affinities can be identified with biota from six contrasting biogeographic regions: Antarctic, bipolar (subarctic and sub-Antarctic), circumantarctic, Gondwana, Neotropical and high Andean, also considering the high degree of endemism. The field environmental philosophy methodological approach (presented in the second group of articles of this special issue of Magallania) contributes both to knowledge and conservation of the small flora of bryophytes and lichens, and other biota that have remained less perceived and valued in Cape Horn and other regions of the world.
Keywords: biogeography; bryophytes; endemism; lichens; subantarctic